Sociālpedagoģiskā darbība savstarpējā skolēnu mobinga mazināšanā Rīgas X vidusskolas 6-8.klasēs. - Inovska, Sandra (Latvijas Universitāte, 2022)
Sandras Inovskas diplomdarbs “Sociālpedagoģiskā darbība savstarpējās skolēnu mobinga mazināšanā Rīgas X vidusskolas 6.-8.klasēs” Diplomdarba mērķis – Raksturot skolēnu savstarpējo mobingu Rīgas X vidusskolas 6.-8.klasēs un izstrādāt sociālpedagoģisko programmu par mobinga mazināšanu, veikt tās aprobāciju un iegūto datu analīzi. Teorētiskajā daļā apskatīts mobinga raksturojums, tā veidi, izpausmes un pazīmes. Tiek raksturotas mobinga lomas, upuru un pāridarītāju pazīmes. Tiek apskatīts sociālpedagoģiskā darbība un sociālā pedagoga loma mobinga mazināšanai skolā. Praktiskajā daļā veikts pētījums Rīgas X vidusskolas 6.-8.klasēs, izstrādāta sociālpedagoģiskās darbības programma savstarpējā skolēnu mobinga mazināšanā Rīgas X vidusskolas 6.-8.klasēs un veikta tās aprobācija ar iegūto rezultātu izvērtējums .

The Diploma Paper of Sandra Inovska “Social pedagocical activities to reduce mutual mobbing of 6-8th grade students of Riga X Secondary School” The aim of the Diploma paper is to describe the mutual mobbing of students in the 6th-8th grades of Riga X Secondary School and to develop a social-pedagogical program on reducing mobbing, to carry out its approbation and analysis of the obtained data. Theoretical part covers characteristics of mobbing, its types, manifestations and signs are examined. Mobbing roles, characteristics of victims and bullies are described. The Socio-pedagogical activity and the role of the social-pedagogue in reducing mobbing at school are discussed. In practical part research was conducted in the 6th-8th grades of Riga X Secondary School, a social-pedagogical activity program was developed to reduce mutual student mobbing in Riga X Secondary School 6th-8th grades, and its approbation was carried out with the evaluation of the obtained results
Social pedagocic activities to reduce mutual mobbing of 6-8th grade students of Riga X Secondary School.
Keywords: Pedagoģija; savstarpējais; skolēnu; mobings; skola; sociālpedagoģiskā